Informed consent in clinical research - Saurabh R Shrivastava; Prateek Shrivastava; Jegadeesh Ramasamy (Wolters Kluwer Medknow Publications, 2015)
Worldwide, the goal of clinical research is to develop knowledge that improves human health or augments understanding of human biology. In biomedical research, two pillars have been identified - informed consent and independent review by an Ethics Committee. Informed consent is a consent given by a competent individual, who is willing to participate in a specific study after being informed about the study, and having made the decision without being subjected to force, undue influence or intimidation. The informed consent form consists of multiple elements, which should be incorporated in the form, and the completeness of the same should be assessed by the Ethics Committee. In conclusion, the practice of obtaining informed consent plays a crucial role in clinical research to safeguard the interests of the study subjects.